(untitled) (Tạp chí Y học Cộng đồng, 2026)
Objective: To evaluate the indications for primary cesarean section at Ha Dong General Hospital in 2024. Subject and method: A cross-sectional descriptive study was conducted on 572 pregnant women with a gestational age ≥ 28 weeks and no prior uterine scar who underwent their first cesarean section at Ha Dong General Hospital from January 2024 to December 2024. Results: The hospital’s cesarean section rate was 54.7%, with primary cesarean sections accounting for 28.1% of total births. Fetal causes were the most common indication (59,3%), primarily due to fetal distress (64,6% in nulliparous and 35.4% in multiparous women). Abnormal labor accounted for 18,0%, with fully dilated cervix but non-engaged head being the main cause, particularly in 62,2% of nulliparous cases. Maternal causes accounted for 9,1%, while adnexal causes represented 7.0%. Social factors (6,6%) were mainly related to infertility/IVF. Regarding clinical characteristics, 80,0% of cases were between 37 and 40 weeks of gestation, 83,2% were in the latent phase of labor, and 61,9% were nulliparous. Conclusion: Indications for primary cesarean section at Ha Dong General Hospital in 2024 were primarily driven by fetal factors, especially fetal distress, and abnormalities in labor progression. Surgical decisions were frequently based on a combination of multiple clinical indications and were mostly performed during the latent phase of labor in full-term pregnancies.